Analysis of the Differences in Host-guest Interaction Willingness and Behavior from the Perspective of the New Generation of Tourists - Luo, Mengran (International Journal of Social Sciences and Public Administration, 2025)
With the generational change of tourism subjects, the new generation of tourists (born after 1990) has gradually become the main force in the tourism market. Their stronger desire for expression, pursuit of individuality and high dependence on digital media have led to their unique behavioral characteristics in the interaction between host and guest. Although this group generally expects to achieve deep communication with local residents, their actual behavior mostly stays at a shallow level of interaction, showing a misalignment phenomenon of "expecting depth but stopping at the surface". Based on the grounded theory, this paper selected 30 new generation tourists for in-depth interviews, identified five core categories of interaction willingness, actual behavior, behavior restriction factors, alternative paths and self-regulation, and constructed a theoretical model of "willingness-behavior misalignment" in the interaction between host and guest of the new generation of tourists. The study found that social anxiety, communication barriers and unfamiliar environment are the key factors that restrict deep interaction. After perception is restricted, tourists tend to rely on digital media for information acquisition and indirect communication, and alleviate the psychological gap through a variety of self-regulation strategies. This study systematically reveals the psychological and behavioral paths of the obstructed transformation of interaction willingness, and provides a new perspective and practical reference for understanding the social behavior characteristics of the new generation of tourists and optimizing tourism experience.